A systematic review of technology-supported scaffoldings in empirical studies from 2017-2022: Trends, scaffolding design features and learning outcomes - Daner Sun; Kee Lee Chou; Lan Yang; Yuqin Yang (Educational Technology & Society, 2024)
This systematic review aims to offer a comprehensive analysis of recent empirical studies on technology-supported scaffoldings (TSS) within the education sector. A total of 31 TSS studies published between 2017 and 2022 were selected from the reputable databases. The analysis focuses on trends, research methods, intervention design, and student learning outcomes in TSS studies. The findings reveal that TSS applications encompass a diverse range of participants, subjects, pedagogical approaches, teaching strategies, and technological tools, impacting cognitive and affective domains. However, recent TSS research demonstrates a bias towards upper primary and junior secondary students, with a focus on science and language subjects. While established e-learning tools are commonly integrated into TSS designs, there is limited exploration of metacognitive and motivational scaffoldings. This study highlights the importance of dynamic scheduling and adjustment of TSS to cater to individual student needs and capabilities, laying the groundwork for future research to develop highly customized TSS that effectively support student learning.